Proportion of life lived with dystonia inversely correlates with response to pallidal deep brain stimulation in both primary and secondary childhood dystonia. (1st March 2013) - Lumsden, Daniel E; Kaminska, Margaret; Gimeno, Hortensia; Tustin, Kylee; Baker, Lesley; Perides, Sarah; Ashkan, Keyoumars; Selway, Richard; Lin, Jean‐Pierre
<x xml:space="preserve">Abstract</x> Aim The aim of this study was to examine the impact of dystonia aetiology and duration, contracture, and age at deep brain stimulation (DBS) surgery on outcome in a cohort of children with medically refractory, disabling primary, secondary‐static, or secondary‐progressive dystonias, including neurodegeneration with brain iron accumulation (NBIA). Method Dystonia severity was assessed using the Burke–Fahn–Marsden Dystonia Rating Scale (BFMDRS) motor score at baseline and 6 and 12 months postoperatively in a cohort of 70 consecutive children undergoing DBS between June 2005 and July 2011. Results Two children (3%) received unilateral DBS for hemidystonia and were excluded and five (7%) developed infections requiring part‐DBS removal within 6 months, leaving 63 children (90%) undergoing bilateral DBS for follow‐up (34 males, 29 females; mean age at surgery for the whole group 10y 4mo, SD 4y 2mo, range 1–14y). Seventeen children were classified with primary dystonia: mean age 12 years 11 months, SD 4 years 6 months range 4 years 6 months to 17 years 3 months; 28 as having secondary‐static dystonia: mean age 10 years 2 months, SD 4 years 9 months (range 3y 3mo–20y); five as having secondary‐progressive dystonia: mean age 8 years 11 months, SD 3 years 9 months (range 5y 5mo–13y 1mo); and 13 as having NBIA dystonia: mean age 10 years 2 months, SD 3 years 11 months (range 1–14y). Children with primary dystonias demonstrated greater improvements in BFMDRS motor score than those in the other aetiological categories (Kruskal–Wallis test, p<0.001), which correlated negatively with dystonia duration and more strongly still against the ratio of dystonia duration normalized to age at surgery (DD/AS ratio) at 1 year (Spearman's rank correlation coefficient 0.4752 and −0.599 respectively). A similar significant negative correlation was found in the secondary‐static dystonia group between outcome at 1 year and DD/AS ratio (−0.461). Poorer outcome in secondary dystonia coincided with the absence of a period of normal motor development in comparison with the primary dystonia group. A significant improvement in BFMDRS motor score was seen in the NBIA group at 6, but not 12 months (Wilcoxon signed rank test p=0.028, p=0.85 respectively). No reduction in efficacy was seen in children with a musculoskeletal deformity at the time of surgery. Conclusion Response to pallidal DBS in the treatment of dystonia declines with the proportion of life lived with dystonia in primary and secondary dystonia. Other intrinsic factors reduce the median magnitude of reduction in secondary dystonia after DBS. DBS should be offered early, preferably within 5 years of onset, to maximize benefits and reduce the childhood experience of dystonia, including musculoskeletal deformity. Other multidimensional assessments are required to understand how DBS improves the lives of children with dystonia.